The impact of the Tracey judgment on the rates and outcomes of in-hospital cardiac arrests in UK hospitals participating in the National Cardiac Arrest Audit - Zenasni, Zohra (Clin Med (Lond), 2020)
AIMS: The aim was to determine if the 17 June 2014 Tracey judgment regarding ‘do not attempt cardiopulmonary resuscitation’ decisions led to increases in the rate of in-hospital cardiac arrests resulting in a resuscitation attempt (IHCA) and/or proportion of resuscitation attempts deemed futile. METHOD: Using UK National Cardiac Arrest Audit data, the IHCA rate and proportion of resuscitation attempts deemed futile were compared for two periods (pre-judgment (01 July 2012 – 16 June 2014, inclusive) and post-judgment (01 July 2014 – 30 June 2016, inclusive)) using interrupted time series analyses. RESULTS: A total of 43,109 IHCAs (115 hospitals) were analysed. There were fewer IHCAs post- than pre-judgment (21,324 vs 21,785, respectively). The IHCA rate was declining over time before the judgment but there was an abrupt and statistically significant increase in the period immediately following the judgment (p<0.001). This was not sustained post-judgment. The proportion of resuscitation attempts deemed futile was smaller post-judgment than pre-judgment (8.2% vs 14.9%, respectively). The rate of attempts deemed futile decreased post-judgment (p<0.001). CONCLUSION: The IHCA rate increased immediately after the Tracey judgment while the proportion of resuscitation attempts deemed futile decreased. The precise mechanisms for these changes are unclear.